Praktik Pembuatan Website Sebagai Media Branding Pantai Markoni Balikpapan - Silfiani, Mega; Nurlaily, Diana; Hayati, Farida Nur; Hermayanti, Naura Attya; Hanifatuzzuhro, Retno Lelly Winda; Firdaus, Andi Adam; Aulia, Aleyda Kania Farra; Wijayanti, Anis Fadillah; Aprilianti, Dwi Savira; Hariyadi, Fahri Dwi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service activity aims to increase the attractiveness of Markoni Beach in Balikpapan through the creation of website-based promotional media as an effort to increase the number of visitors and community welfare. The method of implementing this service used surveys, outreach and practice. The results of this dedication showed that the creation of website media was used as branding for Markoni Balikpapan Beach. It could increase visitors to Markoni Beach. Apart from that, outreach could increase public understanding regarding the importance of processing waste and maintaining environmental cleanliness in tourist areas. It is hoped that the results of this activity could increase the number of visitors and the economic welfare of the local community.